TRANSFORMASI OTORITAS DAKWAH DI ERA DIGITAL: PERGESERAN DARI ULAMA TRADISIONAL KE CONTENT CREATOR RELIGI DI MEDIA SOSIAL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the transformation of communication technology that has shifted the practice of da'wah from conventional to digital spaces, thus giving rise to changes in the structure of religious authority. This study aims to analyze the shift in da'wah authority from traditional ulama to religious content creators and to understand the role of the audience in shaping religious legitimacy on social media. This study uses a qualitative method with a phenomenological approach within an interpretive paradigm, through in-depth interviews, observations of social media activity, and documentation studies. The results show that there has been a shift from authority based on sanad, science, and institutions to digital charismatic authority determined by visibility, engagement, and communication skills, where social media functions as an arena that not only disseminates but also shapes religious legitimacy. The audience acts as an active actor, determining credibility based on ease of understanding, emotional closeness, and practical relevance, making the authority of da'wah more fluid, participatory, and continually negotiated. The discussion confirms that this phenomenon aligns with the theory of authority and the concept of the mediatization of religion, which demonstrates structural and epistemological changes in the production and distribution of religious knowledge. The implications of this research emphasize the importance of communicative adaptation for da'is without neglecting the quality of their knowledge, so that da'wah remains credible, contextual, and responsible in the digital era.